Psychological Biomarkers and Fibrosis: An Innovative Approach to Non-alcoholic Fatty Liver Disease - Funuyet-Salas, Jesús; Pérez-San-Gregorio, María Ángeles; Martín-Rodríguez, Agustín; Romero-Gómez, Manuel (Frontiers in Medicine, 2020)
Background: It is unknown how perceived social support and the progression of liver damage influence the psychosocial profile of patients with nonalcoholic fatty liver disease (NAFLD). In the present study, we therefore investigated which biomarkers influence the quality of life, mental health, and coping strategies of NAFLD patients. Methods: Quality of life (SF-12, CLDQ-NAFLD), mental health (HADS, BDI-II) and coping strategies (COPE-28) were evaluated by high or low perceived social support (MSPSS) and the presence of nonalcoholic steatohepatitis (NASH) and significant fibrosis in 492 biopsy-proven NAFLD patients. Results were compared with quality of life normality tables for the general Spanish population. We also determined whether liver histology and biopsychosocial variables predicted participant quality of life. Results: Interactive effects were found in vitality (p=0.05), activity (p=0.005), anxiety (p=0.04) and denial (p=0.04), with NASH patients showing a higher-risk biopsychosocial profile when they perceived less social support. Furthermore, patients with low perceived social support showed lower quality of life, worse mental health and more maladaptive coping than those with high perceived social support, regardless of NASH presence. Patients with significant fibrosis showed lower quality of life compared to those without or the general Spanish population. Patients with significant fibrosis also reported worse mental health and more maladaptive coping. Lastly, significant fibrosis, female sex, greater anxiety and depressive symptoms, and worse physical and mental health-related quality of life were found to be independent determinants of worse disease-specific quality of life in these patients. Conclusions: Low perceived social support, significant fibrosis and female sex were independently associated with a higher-risk psychosocial profile in NAFLD. These findings support the role of psychological biomarkers based on quality of life, mental health and coping strategies in the management of these patients and suggest the potential benefits of a psychological intervention.